Energy-Aware Dynamic VM Selection With Perfect Workflow Time Scheduling Algorithm - S.Boopalan, Dr. Puneet Goswami (International Journal of Advanced Science and Technology, 2020)
Efficient scheduling workflow for cloud management is proposed here resource provisioning andscheduling heuristics may have different objectives. This work focuses on both energy efficientsupervision of virtual machine and finding a perfect time schedule to execute a workflow in datacentres on IaaS computing resources such that the total execution cost is minimized and the deadlineis met. Depends on the CPU utilisation the server power consumption is computed in large scale datacentres. By detecting and consolidating active VM host and executing the workflow on basis of perfecttime scheduler brings out good energy balancing environment with required Quality of Service.